CONSTRUCTING A NEW INDIA:NATION, MYTH AND SALMAN RUSHDIE’S MIDNIGHT’S CHILDREN - Daniels, Christie (Revista Literatura em Debate, 2013)
National identity at its root attempts to operate as a unifying force in a society. This identity is created through a guiding narrative which is rhetorically constructed. As such, myth plays a central role in the creation of nations and their identities. India, as a relatively new nation, serves as an interesting example of this phenomenon. Nehru in his “A Tryst with Destiny” speech on the eve of independence employs many types of myth as he attempts to unify a nation of the verge of being born. In response, Salman Rushdie dissects and exposes the myths employed by the Indian nation in his novel, Midnight’s Children.CONSTRUINDO UMA NOVA ÍNDIA: NAÇÃO, MITO E OS FILHOS DA MEIA-NOITE, DE SALMAN RUSHDIEA identidade nacional, em sua essência, ambiciona agir como uma força unificadora na sociedade. Tal identidade é criada através de narrativas retoricamente construídas. Assim, o mito ocupa um lugar central na criação das nações e em suas identidades. A Índia, como uma nação relativamente nova, serve como um interessante exemplo desse fenômeno. No seu discurso “Um encontro com o destino,” na véspera da independência, Nehru emprega muitos tipos de mito, em sua tentativa de unificar a nação às vésperas de seu nascimento. Em resposta, Salman Rushdie disseca e expõe os mitos empregados pela nação indiana em seu romance Os filhos da meia-noite.